Flexible electricity generation, grid exchange and storage for the transition to a 100% renewable energy system in Europe - Michael Child; Claudia Kemfert; Dmitrii Bogdanov; Christian Breyer (Renewable Energy, 2019)
Two transition pathways towards a 100% renewable energy (RE) power sector by 2050 are simulated for Europe using the LUT Energy System Transition model. The first is a Regions scenario, whereby regions are modelled independently, and the second is an Area scenario, which has transmission interconnections between regions. Modelling is performed in hourly resolution for 5-year time intervals, from 2015 to 2050, and considers current capacities and ages of power plants, as well as projected increases in future electricity demands. Results of the optimisation suggest that the levelised cost of electricity could fall from the current 69 exteuro/MWh to 56 exteuro/MWh in the Regions scenario and 51 exteuro/MWh in the Area scenario through the adoption of low cost, flexible RE generation and energy storage. Further savings can result from increasing transmission interconnections by a factor of approximately four. This suggests that there is merit in further development of a European Energy Union, one that provides clear governance at a European level, but allows for development that is appropriate for regional contexts. This is the essence of a SuperSmart approach. A 100% RE energy system for Europe is economically competitive, technologically feasible, and consistent with targets of the Paris Agreement.
Keywords: 330; Energy transition; Storage technologies; Europe; 100% Renewable energy; Energy policy